DRY EYE MANAGEMENT IN PATIENTS AFTER CATARACT SURGERY: A LITERATURE REVIEW - Eti - Sumartiyah; Debie Dahlia (International Journal of Nursing and Health Services (IJNHS), 2019)
Cataract surgery is the most common surgical procedure performed to restore visual function due to opacification of the lens. One of the side effects of cataract surgery is the appearance of dry eye symptoms that can occur one to three weeks after surgery. Dry eye symptoms were reduced visual acuity can affect daily work, so that it can interfere with work productivity and quality of life. This paper is a literature review to identify dry eye management in patients after cataract surgery. The search was carried out on Web of Science, EBSCO, PubMed, and Google Scholar. The results showed that the management of dry eyes can be done with drugs, healthy living behaviors especially maintaining eye health and hygiene and also avoiding various risk factors for dry eyes. Assessment of early signs and symptoms of the dry eye needs to be done before surgery so that it can reduce the risk of dry eye events. Management of dry eye in post-cataract surgery patients needs to be done comprehensively so that it can improve the patient's visual ability and a better quality of life. Keywords: cataracts, dry eyes, dry eye management